The Role of the Local Police in Containing the Epidemiological Emergency - Ferrante, David (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
The study proposes an analysis of the role of local police in ensuring the implementation of containment and contrasting measures for the Covid-19 health emergency. Emphasizing how the exclusion from the list of police forces contained in Law 1 April 1981, n. 121, "Nuovo ordinamento dell’Amministrazione della pubblica sicurezza", continue to involve operational uncertainties and require continuous regulatory clarifications, even in situations of maximum urgency such as the pandemiological one.